Conformational biosensors reveal GPCR signalling from endosomes - Irannejad, Roshanak; Tomshine, Jin C.; Tomshine, Jon R.; Chevalier, Michael; Mahoney, Jacob P.; Steyaert, Jan; Rasmussen, Søren G. F.; Sunahara, Roger K.; El-Samad, Hana; Huang, Bo; von Zastrow, Mark (Nature (London), 2013)
Conformation-specific antibodies capable of monitoring the activation state of a G-protein-coupled seven-transmembrane receptor, the β 2 -adrenoceptor, reveals receptor and G-protein activation not only in the plasma membrane, but also in the endosome. Adrenoceptor signalling linked to endosomes It is widely assumed that G-protein-linked signalling occurs only at the plasma membrane. In this study, Mark von Zastrow and colleagues use conformation-specific single-chain antibodies to directly probe the activation of the β2-adrenoceptor, which is a prototypical G-protein-coupled receptor, and its cognate G protein, G s , in living cells. They show that classical or canonical G-protein-linked signalling occurs from endosomes as well as from the plasma membrane. A long-held tenet of molecular pharmacology is that canonical signal transduction mediated by G-protein-coupled receptor (GPCR) coupling to heterotrimeric G proteins is confined to the plasma membrane. Evidence supporting this traditional view is based on analytical methods that provide limited or no subcellular resolution 1 . It has been subsequently proposed that signalling by internalized GPCRs is restricted to G-protein-independent mechanisms such as scaffolding by arrestins 2 , 3 , or GPCR activation elicits a discrete form of persistent G protein signalling 4 , 5 , 6 , 7 , 8 , 9 , or that internalized GPCRs can indeed contribute to the acute G-protein-mediated response 10 . Evidence supporting these various latter hypotheses is indirect or subject to alternative interpretation, and it remains unknown if endosome-localized GPCRs are even present in an active form. Here we describe the application of conformation-specific single-domain antibodies (nanobodies) to directly probe activation of the β 2 -adrenoceptor, a prototypical GPCR 11 , and its cognate G protein, G s (ref. 12 ), in living mammalian cells. We show that the adrenergic agonist isoprenaline promotes receptor and G protein activation in the plasma membrane as expected, but also in the early endosome membrane, and that internalized receptors contribute to the overall cellular cyclic AMP response within several minutes after agonist application. These findings provide direct support for the hypothesis that canonical GPCR signalling occurs from endosomes as well as the plasma membrane, and suggest a versatile strategy for probing dynamic conformational change in vivo .